Pengaruh Kemandirian Belajar terhadap Hasil Belajar Peserta Didik Dimediasi Motivasi Belajar pada SMA Negeri Jakarta Timur - Lutfia Anisa Cahyaningsih; I Ketut R. Sudiarditha; Fitra Dila Lestari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to identify, measure, and analyze the influence of learning independence on student learning outcomes with learning motivation as a mediator in public high schools in East Jakarta. This study involves 10th-grade students from 3 (three) public high schools in East Jakarta based on different categories, with a total of 273 respondents selected through the Simple Random Sampling technique. The approach used in this study is quantitative, and data analysis was conducted using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method through SmartPLS version 4.0 software. The results of the hypothesis testing show that, 1) learning independence has a positive and significant effect on learning outcomes, 2) learning independence has a positive and significant effect on learning motivation, 3) learning motivation has a negative and significant effect on learning outcomes, and 4) learning independence has a negative and significant effect on learning outcomes through the indirect influence of learning motivation. This study shows the involvement of other more dominant factors as mediating variables in the relationship between learning independence and student learning outcomes.